MedEMT : a learning system for prehospital care / Mark G Wills; Grant B Goold; K Lee Watson - Wills, Mark G.
Addresses the Department of Transportation's National Standard Curriculum for training EMT-Basics. This text describes various skills and procedures, including illustrations, study aids of EMTs. It is useful for students involved in ambulance services, fire and police departments, rescue squads, and corporate safety and military personnel.